1988
DOI: 10.1055/s-0038-1647631
|View full text |Cite
|
Sign up to set email alerts
|

Placental Transfer of Vitamin K1 and Its Implications in Fetal Hemostasis

Abstract: SummaryVitamin K status was evaluated using coagulation studies and/ or vitamin IQ assays in a total of 53 normal fetuses and 47 neonates. Second trimester fetal blood samples were obtained for prenatal diagnosis under ultrasound guidance. Endogenous vitamin K1 concentrations (determined by high performance liquid chromatography) were substantially lower than maternal levels. The mean maternal-fetal gradient was 14-fold at mid trimester and 18-fold at birth. Despite low vitamin K levels, descarboxy prothrombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 20 publications
(15 reference statements)
3
29
0
1
Order By: Relevance
“…In the majority of cases, maternal vitamin K deficiency was presumed likely based on the medical histories, but not documented. Since fetal vitamin K levels are normally low due to reduced placental transport, a deficiency in the mother would be expected to further reduce fetal vitamin K levels [Mandelbrot et al, 1988]. Finally, eight infants with CDPX1-like phenotypes born to six mothers with systemic lupus erythematosus (SLE) have been described [Kozlowski et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of cases, maternal vitamin K deficiency was presumed likely based on the medical histories, but not documented. Since fetal vitamin K levels are normally low due to reduced placental transport, a deficiency in the mother would be expected to further reduce fetal vitamin K levels [Mandelbrot et al, 1988]. Finally, eight infants with CDPX1-like phenotypes born to six mothers with systemic lupus erythematosus (SLE) have been described [Kozlowski et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…5 In these experiments, all missense alleles had negligible activity. 9,10 Considering the phenotypic resemblance of warfarin embryopathy in early gestation to BCP, Franco et al 5 (1995) demonstrated that ARSE activity is inhibited in the presence of warfarin, an anticoagulant drug that decreases amounts of active vitamin K. These findings suggested that cases of BCP without ARSE mutations could be caused by inhibition of a normal ARSE enzyme in fetal development by reducing levels of vitamin K. Because placental transport of vitamin K is normally reduced, 11 vitamin K deficiency in the mother would be expected to result in greater vitamin K deficiency in the fetus. This hypothesis is attractive given that there have been several reports of BCP in offspring of both sexes in which gestational vitamin K deficiency was suspected, including mothers with severe hyperemesis gravidarum, 12 small-intestinal obstruction, 13 small-bowel syndrome, 14 pancreatitis, 15 or biliary lithiasis.…”
Section: Original Research Article © American College Of Medical Genementioning
confidence: 99%
“…The placenta maintains a steep gradient of vitamin K during gestation, with fetal levels approximately one-10th that of maternal (51,52). Evidence for vitamin K deficiency at birth has been reported by many authors (52,53).…”
Section: Coagulation Proteins In the Lambmentioning
confidence: 99%
“…Evidence for vitamin K deficiency at birth has been reported by many authors (52,53). It has been speculated that high concentrations of vitamin K promote mutagenesis of DNA in vitro, and low levels of vitamin K are maintained during fetal development to diminish mutagenic risk in rapidly proliferating cells (54).…”
Section: Coagulation Proteins In the Lambmentioning
confidence: 99%